The progression of computed tomographic (CT) images in patients with coronavirus disease (COVID-19) pneumonia: Running title: The CT progression of COVID-19 pneumonia. Issue 6 (June 2020) - Lei, Pinggui; Fan, Bing; Mao, Jujiang; Wei, Jiangping; Wang, Pingxian
Highlights: Of the 49 patients, 89.8% (44/49) patients had a typical transition from early stage to advanced stage, and then from advanced stage to dissipating stage. With the evidence of fibrosis for progression of CT results, 42.9% (21/49) patients developed fibrosis whereas 57.1% (28/49) patients demonstrated no definite fibrosis. Patients with fibrosis in follow CT were older (mean age, 45.4 vs. 33.8 years), with longer LOS (19.1 vs. 15.0 days), and higher rate of ICU admission (19.0% [4/21] vs. 3.6% [1/28]) than that of those without fibrosis.